ELICITING FAMILY BUSINESS OWNERS ATTITUDE AND PROFESSIONALISM TOWARDS BUSINESS PERFORMANCES - Dewi, Liliana; Santoso, Eko Budi; Laturette, Kazia; Wahjudono, Denny Bernardus Kurnia (Jurnal Aplikasi Manajemen, 2019)
This study is eliciting a family business of family business owners'attitude and professionalism towards business performances. To analyze the results, we used a method of Multiple Regression statistical software applied to data from 48 Indonesian family businesses. The first important contribution of this work is that Family Business Owners Attitude increase Business Performances increase too. The second contribution is that Professionalism increase Business Performances increase also. Finally, the third contribution of this work is that Owner Responsibilities influence on the performance of family businesses.